Interuniversity Microelectronics Center (IMEC) (B) - Chesbrough, Henry William; Vanhaverbeke, Wim; Odusanya, Lola (London : SAGE Publications Ltd, 2017)
The IMEC case study allows students to discuss open innovation in the context of research organizations with industry partnerships. Johan Van Helleputte, the Vice President of Strategic Management at Interuniversity Microelectrics Center (IMEC), a European research institute that focuses on advanced microelectronics research for applications in the semiconductor industry, is on the verge of presenting a growth strategy to his Board for approval. With the assistance of his team, Val Helleputte had discussed whether to develop an advanced 300 mm wafer research laboratory that would require an investment of more than $1 billion. If a decision were made to go through with this investment, three primary challenges would need to be met: 1) raising the necessary capital to fund the investment, 2) managing the intellectual property arising from the project, and 3) engaging IMECs industry partners in the project.
Originally published in Chesbrough, H., Vanhaverbeke, W., & Odusanya, L. (2009). Interuniversity Microelectronics Center (IMEC) (B). The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Interuniversity Microelectrics Center; Business planning -- Case studies; Strategic planning -- Case studies; Research institutes -- Case studies